(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
This article defines the term «financial condition of an enterprise». The role of assessing the financial condition of an enterprise to study its competitiveness is considered. An attempt has been made to study the mechanisms and methods of assessing the financial condition of an enterprise.